Detection of Honeybee Viruses in Vespa orientalis - Power, Karen; Altamura, Gennaro; Martano, Manuela; Maiolino, Paola (Frontiers in Cellular and Infection Microbiology, 2022)
The Oriental hornet (Vespa orientalis) is spreading across the Italian territory threatening the health and wellbeing of honeybees by feeding on adult individuals and larvae and by plundering hive resources. Considering the capacity of other hornets in harboring honeybee viruses, the aim of this study was to identify the possible role of the Oriental hornet as a vector for honeybee viruses. Adult hornets were subjected to macroscopical examination to identify the presence of lesions, and to biomolecular investigation to detect the presence of six honeybee viruses: Acute Bee Paralysis Virus (ABPV), Black Queen Cell Virus (BQCV), Chronic Bee Paralysis Virus (CBPV), Deformed Wing Virus (DWV), Kashmir Bee Virus (KBV), Sac Brood Virus (SBV). No macroscopical alterations were found while biomolecular results showed that DWV was the most detected virus (25/30), followed by ABPV (19/30), BQCV (13/30), KBV (1/30) and SBV (1/30). No sample was found positive for CBPV. In 20/30 samples several co-infections were identified. The most frequent (17/30) was the association between DWV and ABPV, often associated to BQCV (9/17). One sample (1/30) showed the presence of four different viruses namely DWV, ABPV, BQCV and KBV. The detected viruses are the most widespread in apiaries across the Italian territory suggesting the possible passage from honeybees to V. orientalis, by predation of infected adult honeybees and larvae, and cannibalization of their carcasses. However, to date, it is still not clear if these viruses are replicative but we can suggest a role as mechanical vector of V. orientalis in spreading these viruses.